Does living density matter for nonfatal unintentional home injury in Asian urban settings? Evidence from Hong Kong. - Chan, E; Kim, J; Griffiths, S; Lau, J; Yu, I (2009)
Injury is a major global disease burden for the twenty-first century. There are, however, few studies of unintentional household injury in Asian urban settings where living environments are characterized by extremely compact, high-living-density, multistory apartments. This study investigated the association between nonfatal unintentional household injuries with the resident's sociodemographic attributes and household characteristics in Hong Kong, the city with the world's highest population density. A cross-sectional retrospective recall study was conducted in May 2007 using a random telephone survey with a modified Chinese version of the World Health Organization Injury and Violence instrument. The study sample included 1,001 noninstitutionalized Cantonese-speaking Hong Kong residents of all ages, including foreign live-in domestic helpers. Multivariate regression was conducted to identify risk factors for nonfatal unintentional injuries in Hong Kong. Among a predominantly adult sample, household size and time spent at home were not associated with nonfatal unintentional household injuries in the general population in Hong Kong. The multivariate analyses indicated that female gender, owners of private homes, lower square footage of living space per person, and those with slip prevention devices in the bathroom were significantly associated with household injuries. Injured and noninjured groups were found to have adopted different injury prevention strategies toward household injuries. The results identified potential target groups for household injury prevention programs.